On the use of Modulated Temperature Differential Scanning Calorimetry to assess wax crystallization in crude oils. (15th August 2017) - Paiva, Felipe L.; Calado, Verônica M.A.; Marchesini, Flávio H.
Abstract: In this paper, measurements of the Wax Precipitation Temperature (WPT) of waxy crude oil samples by a type of Modulated Temperature Differential Scanning Calorimetry, commercially termed StepScan™ (SSDSC), are reported. Repeatable and reliable measurements of WPT by SSDSC are found to depend on specific experimental cooling parameters used with this technique. When appropriate parameters are used, two exothermic peaks can be detected on the non-reversing component and one peak on the reversing component (RC) of SSDSC thermograms. We also present indications that the onset of the peak on RC is related to the change in phase angle detected by sinusoidal temperature modulation programs and that it likely does not correspond to a measurement of the WPT. Additionally, by further adjusting SSDSC experimental parameters, because SSDSC is not based on a sinusoidal temperature modulation, reproduction of SSDSC cooling programs by rheometry and Polarized Light Microscopy (PLM) is possible. It was found that the different values used for the SSDSC cooling parameters, when reproduced on the rheometer, do not impact the oil's rheology significantly at the applied shear rate. Moreover, it is shown that the onset of the peak detected on the RC portion of SSDSC thermograms is associated with a significant increase in average wax crystal number, as indicated by microscopy; while the consequences on average wax crystal size are found to depend on the initial cooling temperature. Furthermore, comparisons of WPT determination by SSDSC and by conventional DSC analysis show the potential of SSDSC in obtaining comparable and more reliable WPT measurements depending on crude oil composition and SSDSC cooling parameters.